(untitled) (International relations and international law Journal, 2016)
Family and childhood institutions acquire increased public importance in the current socio-demographic situation in the world which requires the necessity of establishing an appropriate system of legal protection. As everybody knows, a large number of Kazakh children were adopted by foreign nationals. Foreign adoption as a form placement of orphaned children is an important mechanism of state protection, the most unprotected and vulnerable group – children. This institution should be on the side of children’s interests and protect the rights of the child as much as possible, rather than working as a lever diplomatic game . Nevertheless, the practice of practice of foreign adoptions shows the world new violations of the rights of orphans in an overseas. Despite of a huge number of international conventions relating to adoption and the rights of the children, there are still many unresolved issues that must be resolved. This article reveals the problems that arise in adoption of children by foreign citizens from Kazakhstan concerning the law applicable to the settlement of contentious issues between states. We offer new solutions to deficiencies of international and national legislation on the experience of the advanced countries.